ASSESSING WATER QUALITY AND THE NON-CARCINOGENIC HEALTH RISKS OF SURFACE AND GROUNDWATER IN IBI – TARABA STATE - Ojimma, Benjamin; Joshua, Williams (FUDMA JOURNAL OF SCIENCES, 2022)
The high concentration of chemical and biological contaminants in rural water is known to cause waterborne and water-related diseases. This study provides insights into the quality of surface and groundwater used for consumption and other domestic uses in Ibi environs. It further assesses the association between water quality variables and evaluates the chronic non-carcinogenic health risk using hazard quotient and hazard index. Thirty water samples each from the river and hand-dug wells were collected and the values of 17 variables were measured. The results showed that 58.8% and 35.3% of surface and groundwater failed to conform to national drinking water guidelines. The result for correlation between measured variables indicates both positive and negative correlation between variables across both water sources with pH negatively correlating with turbidity (r = -0.832) and TDS (r = -0.714) while temperature correlated positively with turbidity (r = 0.925), TDS (r = 0.793) and TH (r = 0.847). The results of human health risk show NO3- as the most dominant variable in inducing non-carcinogenic health risk in surface water while F- was the most inducing variable for groundwater. Based on the THI values, all the water sources showed long-term health risks above the safe limit even though some of the variables were within the national standards. There is therefore the need to address agricultural activities which is likely the major cause of nitrate in drinking water within the study region.